Study of hull girder ultimate strength at elevated temperatures. (18th August 2021) - Fanourgakis, Stamatios; Samuelides, Manolis
ABSTRACT: Fire poses a significant threat in the shipping industry not only for humans (passenger, seafarers) but also for the ship structure. It is of great concern how elevated temperatures from a fire can influence the bending moment capacity of a hull girder due to the degradation of steel's mechanical properties. The aim of the paper is to evaluate the ultimate bending moment capacity of a chemical oil/product carrier at ambient and elevated temperature conditions. The study defines the parameters and modelling that need to be considered in the finite element analysis (FEA) and proposes a modified incremental–iterative procedure for the bending moment capacity calculation at elevated temperatures. Smith Method was extended in order to incorporate neutral axis rotation and steel's mechanical properties at elevated temperatures. The proposed modified Smith Method's results present good agreement with the equivalent FEA results. It is concluded that with the proposed modified Smith Method, it is possible to determine the loading that can be carried by a hull girder with a specified temperature profile. The study also determines an analysis technique for the stiffened panel ultimate strength analysis at elevated temperatures.